MIKROBA ENDOFIT âSI PEMBUNUHâ Escherichia coli - Walpajri, Febri; Rohyani, Rohyani; Umayah, Sari (Program Kreativitas Mahasiswa - Penelitian, 2014)
Endophytic microbes are microscopic microorganisms (bacteria and fungi) that live in the tissues of plants, leaves, roots, fruits and stems. The parasite plants (Helixanthera sp.) on sapodilla (Manilkara zapota), cocoa (Theobroma cacao) and coffee (Coffea arabica) are medicinal plants. These plants have endophytic microbes that have antibacterial compounds as antibiotics. The purpose of this study was to get endophytic microbial isolates from parasite plants (Helixanthera sp.) on sapodilla, cocoa and coffee, and determine the antibacterial activity against Escherichia coli. Sampling was conducted in Kampar regency and Pekanbaru city. The parasite plants were collected from the field and their endophytic microbes were isolated using surface sterilization method and purified before being tested the activity against E. coli. The selected microbes were then characterized. The results obtained 30 endophytic bacterial isolates and 10 endophytic fungi that had activity against E. coli. Endophytic bacteria isolate which had the highest activity against E. coli was Bbs4 isolate from sapodilla parasites with 12,1 mm inhibition zone diameter and endophytic fungi isolate which had the highest activity against E. coli was Jbc2 isolate (genus Penicillium) from cocoa parasites with 12,1 mm inhibition zone diameter. Keywords: antibacterial, endophytic microbes, Escherichia coli, parasite plant